A revisit of the semi-geostrophic eddy east of the Sri Lanka dome with anisotropy insight - Le, Zhou; Subrahmanyam, M. V.; Raju, Pemmani Venkata Subba; Pathirana, Gayan; Wang, Dongxiao; Song, Wei (Frontiers in Marine Science, 2025)
During boreal summer, the Southwest Monsoon Current (SMC) turns northeastward, transporting highly saline water into the Bay of Bengal (BOB) and significantly influencing the dynamics of the upper ocean. Previous studies have shown that an anticyclonic semi-geostrophic (SG) eddy forms on the eastern flank of the SMC, this formation associated with the kinetic energy transfer via the barotropic instability (BTI). The presence of such an eddy can attenuate the meridional salinity flux, potentially affecting the development of the circulation within the BOB. Acknowledging the importance of this phenomenon, this study revisits the SG eddy using satellite altimetry data, reanalysis datasets and in-situ observations from the Research Moored Array for African-Asian-Australian Monsoon Analysis and Prediction (RAMA) project. Our results show that a cyclonic eddy-like (CE-like) negative Sea Level Anomaly (SLA), generated in the eastern BOB due to regional anomalous wind stress curl, also contributes to the formation of the SG eddy. During the formation, mean flows on the northern edge of the SG eddy are strengthened, while southeastward currents on the eastern edge are structured influenced by CE-like SLA. Further instability analyses indicate that the anisotropic component of BTI is significantly larger than the isotropic component, which is attributed to the weak nonlinear planetary geostrophic convergence of the SG eddy and the strong horizontal shear in mean flow field induced by CE-like SLA. Additionally, our results point out that anomalies in wind stress curl over the eastern BOB and subsequent formation of negative SLA are likely influenced by the Indian Ocean Dipole. These findings suggest that the coupling between SMC instability and regional wind stress curl may play a pivotal role in the generation of SG eddy on interannual timescale, with important implications for regional ocean dynamics.